Revealing the Readiness of Pet Shops in Bandung City to Adopt Private Entity SAK: Internal and External Factor Analysis - Daniel Nababan; Ivan Gumilar Sambas Putra; Yana Hendayana (Cita konsultindo, 2026)
The adoption of standardized financial accounting practices remains a major challenge for micro, small, and medium enterprises (MSMEs) in Indonesia, particularly in sector-specific businesses such as pet shops that operate with relatively complex transactions. This study aims to examine the readiness of pet shop MSMEs in Bandung City to adopt Private Entity Financial Accounting Standards (SAK) by analyzing the influence of technology readiness, human resource competency, and external support on financial accounting system implementation. The study employs a quantitative research design using primary data collected through structured questionnaires distributed to 90 pet shop owners and managers. Data were analyzed using multiple linear regression supported by classical assumption testing. The results show that technology readiness, human resource competency, and external support all have positive and statistically significant effects on financial accounting system implementation. Among these factors, technology readiness emerges as the most dominant determinant, followed by human resource competency and external support. The findings indicate that readiness to adopt Private Entity SAK is primarily capability-driven rather than regulation-driven, reflecting a gradual process shaped by internal organizational preparedness and reinforced by external facilitation. This study contributes to the MSME accounting literature by providing empirical evidence from a relatively underexplored business sector and offers practical insights for policymakers and supporting institutions in designing more effective and context-sensitive strategies to enhance accounting standard adoption among micro-enterprises.